Histopathological evidence of immunological and pseudoimmunological reactions by transplantation of embryonic and foetal nervous tissue in experimental conditions - Rozhold, Odolen; Nádvorník, P (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1990)
The analysis of 11 unsuccessful transplantation of embryonal nervous tissue into recipient brain gives the possibility to distinguish the immunological rejection from the pseudoimmunological response, conditioned by simple tissue necrosis. It is necessary to calculate not only with the antigenous character of tissue, but also with the grow potency and the nourishment of the graft in the recipient brain.
Keywords: Transplantation, Heterologous; kočky; Fetal Tissue Transplantation; Brain; Transplantation, Homologous; transplantace mozkové tkáně; Graft Rejection; Brain Tissue Transplantation; autologní transplantace; homologní transplantace; Animals; lidé; transplantace fetální tkáně; Humans; zvířata; rejekce štěpu; mozek; Transplantation, Autologous; Cats; transplantace heterologní